Efficacy of Dietary Supplements on Sleep Quality and Daytime Function of Shift Workers: A Systematic Review and Meta-Analysis - Wu, Yeqi; Huang, Xueyan; Zhong, Congcong; Wu, Ting; Sun, Dai; Wang, Rui; Zhan, Qiang; Luo, Huasong (Frontiers in Nutrition, 2022)
Background: Dietary supplements (DSs) may be useful for managing shift work disorder (SWD), but their efficacy in non-simulated shift populations remains controversial. This review explores the potential role of DSs for improving sleep quality, daily functioning, and mood among shift workers in the real world. Methods: A related literature search was conducted in PubMed, Web of Science, Embase, and Cochrane Library databases from their inception to July 2021. Information was collected on “shift work,” “irregular working hours,” “night shift,” “dietary supplements,” and “nutraceutical research data.” Sleep quality-related scales were the primary outcome measures. The meta-analysis was conducted using RevMan 5.4 (Cochrane Collaboration, London, England) and Stata 15.0 (StataCorp, LLC, College Station, TX, USA). Heterogeneity was examined by using I2 statistics, and publication bias was assessed via Egger's regression test. Results: Twelve studies, which involved 917 participants, met the inclusion criteria. The DS groups had significant improvement in sleep quality scores (8 randomized controlled trials [RCTs]: p = 0.04; standard mean difference (SMD), -0.45 [-0.88 to -0.03]) and daytime function (7 RCTs: p = 0.02; SMD, -0.50 [-0.92 to -0.08]). The DS groups did not have a significant improvement in psychomotor vigilance (4 RCTs: p = 0.25; SMD, 0.52 [-0.36 to 1.41]), depression (5 RCTs: p = 0.14; SMD, -0.19 [-0.45 to 0.06]), or anxiety (4 RCTs: p = 0.27; SMD, -0.23 [-0.65 to 0.18]). All RCTs suggested a positive safety profile for DSs. Conclusions: The findings of this meta-analysis indicated DSs may be beneficial for improving sleep quality and daytime function in shift workers. Although there is a wide range of DSs, the small amount of literature included for each type does not allow for subgroup analysis to be used to eliminate high heterogeneity. We have not yet included literatures on other languages either. Given these limitations of the study, there is still a need for more well-designed RCTs so that our review can be updated in the future to make the results more conclusive.